A new closed-form thermodynamic model for thermal simulation of spark ignition internal combustion engines. (15th November 2015) - Barjaneh, Afshin; Sayyaadi, Hoseyn
Highlights: A new closed-form thermal model was developed for SI engines. Various irreversibilities of real engines were integrated into the model. The accuracy of the model was examined on two real SI engines. The superiority of the model to previous closed-form models was shown. Accuracy and losses were studied over the operating range of engines. Abstract: A closed form model based on finite speed thermodynamics, FST, modified to consider various losses was developed on Otto cycle. In this regard, the governing equations of the finite speed thermodynamics were developed for expansion/compression processes while heat absorption/rejection of the Otto cycle was determined based on finite time thermodynamics, FTT. In addition, other irreversibility including power loss caused by heat transfer through the cylinder walls and irreversibility due to throttling process was integrated into the model. The developed model was verified by implementing on two different spark ignition internal combustion engines and the results of modeling were compared with experimental results as well as FTT model. It was found that the developed model was not only very simple in use like a closed form thermodynamic model, but also it models a real spark ignition engine with reasonable accuracy. The error in predicting the output power at rated operating range of the engine was 39%, while in the case of the FTT model, this figure was 167.5%. This comparison for predicting thermal efficiency was +7% error (as difference) for the developed model compared to +39.4% error of FTT model.